Use of the covered internal prosthesis in the Treatment of the arterial traumas - علي سليمان (Latakia University Journal -Medical Sciences Series, 2021)
Recently, there have been many arterial traumas caused by gunshot or wounds, especially in the circumstances of the Syrian war, which caused arterial blockage, false aneurysms or arterio-venous fistulas. The method of treatment of these injuries stopped at the time of injury and the presence of other accompanying injuries in addition to medical expertise and the availability of the necessary materials and specialized medical centers. In some cases, the patient’s condition is generally stable, so the patient is a candidate for subsequent treatment using the covered internal prosthesis as a better option to avoid the risk of traditional surgical interference, and this internal prosthesis serve to perform arterial repair (whether false aneurysms or arterio-venous fistulas) through an entrance far from the site of injury.